Penggunaan Aplikasi Online Quizizz dalam Menganalisis Hasil Tes Kognitif Siswa pada Materi Energi - Lusiani Lusiani (SPEJ (Science and Physic Education Journal), 2020)
The purpose of this study was to analyze the results of students' cognitive tests on energy using the Quizizz application in online learning. This research method is in the form of survey research and literature review. Sampling was carried out using random sampling in order to obtain 28 vocational students in the physics subject matter of energy, but two of them experienced problems so that they could not take the test of learning outcomes in energy material. The analysis of cognitive test results is described quantitatively with descriptions of images and graphs of media Quizzes. The results showed that as many as 26 SMK students could answer questions correctly on the energy material in some of the questions presented. The analysis of the most correct answers and the fastest time to answer is in the fifth question, 25 correct answers are obtained within 2 seconds, while the least correct answers and the longest answer are in the tenth question with 8 correct answers within 16 seconds. Students can answer questions in the form of theory that are displayed in picture form, while students have difficulty answering questions in the form of mathematical calculations using certain formulas related to energy even though the pictures have been shown as a way to facilitate understanding of the questions. In conclusion, the use of the Quizizz application provides an idea to educators that the learning outcomes of students' cognitive tests can be easily obtained in a fast time to get an evaluation of learning outcomes, so it can be recommended as a medium for evaluating learning in various fields and various subject matter. Keywords: Energy, Online Learning, Quizizz, Cognitive Tests